Individual differences in expecting coherence relations: Exploring the variability in sensitivity to contextual signals in discourse. Issue 10 (25th November 2020) - Scholman, Merel C. J.; Demberg, Vera; Sanders, Ted J. M.
ABSTRACT: The current study investigated how a contextual list signal influences comprehenders' inference generation of upcoming discourse relations and whether individual differences in working memory capacity and linguistic experience influence the generation of these inferences. Participants were asked to complete two-sentence stories, the first sentence of which contained an expression of quantity ( a few, multiple ). Several individual-difference measures were calculated to explore whether individual characteristics can explain the sensitivity to the contextual list signal. The results revealed that participants were sensitive to a contextual list signal (i.e., they provided list continuations), and this sensitivity was modulated by the participants' linguistic experience, as measured by an author recognition test. The results showed no evidence that working memory affected participants' responses. These results extend prior research by showing that contextual signals influence participants' coherence-relation-inference generation. Further, the results of the current study emphasize the importance of individual reader characteristics when it comes to coherence-relation inferences.